(untitled) (Pedagogy of Higher and Secondary Education, 2011)
The article deals with the synergy ideas that may be used in the organization of the philological non-formal education. The application of the synergy ideas in teaching and upbringing process will help to harmonize the intellectual and emotional factors in learning, which will finally lead to upbringing a personality able to self-actualization, professional growth and mobility in modern society.